2021
DOI: 10.1002/bmc.5150
|View full text |Cite
|
Sign up to set email alerts
|

A new simple method for quantification of cilostazol and its active metabolite in human plasma by LC–MS/MS: Application to pharmacokinetics of cilostazol associated with CYP genotypes in healthy Chinese population

Abstract: A simple, sensitive, and fully automated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the simultaneous quantification of cilostazol (CIL) and its active metabolite, 3,4-dehydro cilostazol (CIL-M), in human plasma. Plasma samples were processed by protein precipitation in 2 mL 96-deep-well plates, and all liquid transfer steps were performed through robotic liquid handling workstation, enabling the whole procedure fast, compared to the reported methods. Separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…LC-MS/MS method is gradually applied for the detection of CLZ and its metabolites along with mass spectrometry development. Two studies reported UPLC-MS/MS method to simultaneously detect CLZ and 3,4-CLZ in human plasma ( Bhatt et al, 2015 ; Shen et al, 2021 ). However, only one metabolite detection in human plasma resulted in the application of pharmacokinetic research under restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS/MS method is gradually applied for the detection of CLZ and its metabolites along with mass spectrometry development. Two studies reported UPLC-MS/MS method to simultaneously detect CLZ and 3,4-CLZ in human plasma ( Bhatt et al, 2015 ; Shen et al, 2021 ). However, only one metabolite detection in human plasma resulted in the application of pharmacokinetic research under restrictions.…”
Section: Introductionmentioning
confidence: 99%